Own Your Walls: Portraiture and Researcher Reflexive Collage Self-Portraits. (January 2021) - Lahman, Maria K. E.; De Oliveira, Becky; Cox, Dannon; Sebastian, Margaret L.; Cadogan, Kimberley; Rundle Kahn, Amber; Lafferty, Mel; Morgan, Michelle; Thapa, Kritika; Thomas, Rowen; Zakotnik-Gutierrez, Jennifer
As part of an advanced doctoral research course, class members participated in an in-depth exploration of the methodology portraiture. In this article, the authors—course instructor and 10 students—represent themselves as researchers through collage portraits and written reflexive responses. A brief review of portraiture, collage in research, and researcher reflexivity, along with descriptions of relevant course experiences are presented. Images of the collage process and resulting portraits are highlighted. A collage portrait of a class emerges as issues of transparency in research, the role of the researcher, and the use of art in research are explored.